Psychotraining of Readiness of Students to Self-Educational Activity - Martynuik, Iryna (Psychological Prospects Journal, 2017)
The article states that on the basis of the author’s pilot study of students’ self-education activity there is a significant percentage of students of different courses who do not practise self-education activity. The mentioned above students are not concerned about their self-improvement, they lack of self-education goal and do not seek and do not master new social experience. Additionally, they do not recognize personal significance in self-education activities, do not demonstrate independence and initiativity while searching for new information, have no stability of interest to a particular experience. The necessity of development of students' readiness for self-education is emphasized. The author examined the essence of readiness for self-education activity (stable psychological formation, which integrates personal qualities, abilities, motivation, knowledge, skills, skills necessary for this activity. This formation revealsa sa willingness for self-education and ensures its effectiveness). In addition, the author analyzed main indicators of the psychological formation: understanding of the meaning of self-education, a positive assessment of the need for self-education, a stable cognitive interest in a particular field of knowledge, etc. The author offered to deliver training on readiness for self-educational activity, which can be applied in practice of educational work with students of higher educational institutions. The detailed outline of this training was presented. The author described the results of the approbation of the mentioned training, which prove its focus on actualization and development of readiness for self-education activity. It gave reasons to speak about its effectiveness in solving the problem of the development of this personality formation in student's youth. The prospects for follow-up researches on this direction  (the analysis of long-term results of the described training, development of a complex of psychological events for the development of students' readiness for self-education activity) are stated.
Keywords: readiness for self-education; psychotraining; self-education; self-education activity; students.